A new rolling culture‐based in vitro fertilization system capable of reducing polyspermy in porcine oocytes. (30th November 2014) - Kitaji, Hideki; Ookutsu, Shoji; Sato, Masahiro; Miyoshi, Kazuchika
Abstract The high incidence of polyspermy is one of the major obstacles during in vitro fertilization (IVF) in pigs. To overcome this, we developed a novel IVF method, which involves constant rotation. Oocytes matured in vitro were mixed with spermatozoa (0.2 × 105 sperm/mL) in an IVF medium (200 μL) using a 200 μL PCR tube. This tube was then rotated at 1 rpm for 6 h at 38.5°C in a rotation mixer (experimental group). A second PCR tube was simultaneously cultured without rotation (control group). The rate of polyspermy was evaluated 12 h after insemination and was significantly (P < 0.05; 21.0% vs. 48.3%) lower in the experimental group than in the control group. Sperm penetration rate was similar in oocytes from the experimental and control groups (75.2% vs. 83.1%). However, monospermic fertilization rate of the oocytes was significantly (P < 0.05; 44.8% vs. 21.2%) higher in the experimental group than in the control group. Furthermore, the rate of blastocyst formation (30.1% vs. 20.8%) increased in the experimental group, as compared to the control group. This present system will contribute to increase the efficacy of blastocyst production through reduction of polyspermic penetration.